2023
DOI: 10.1002/aelm.202300583
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Processed Ternary Organic Photodetectors with Ambipolar Small‐Bandgap Polymer for Near‐Infrared Sensing

Gurudutt Bhat,
Marcin Kielar,
Pankaj Sah
et al.

Abstract: Organic photodetectors (OPDs) detecting light in the near‐infrared (NIR) range from 900 to 1200 nm offer numerous applications in biomedical imaging and health monitoring. However, an ultra‐low bandgap of the electron donor compound required to achieve NIR detection poses a unique challenge in selecting a complementary acceptor material with a suitable energy‐level offset. To tackle this, a solution‐processed, fullerene‐dominated, ternary device is engineered by adding an ultra‐low bandgap (0.6–0.8 eV) ambipol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Our overall performance analyses of OPD with PDINO as a hybrid blend in ETL indicate that PDINO significantly contributes as a cathode interlayer. For comparison of our results, Table provides a list of the recent state-of-the-art reports on high-performance NIR-OPD while Figure S11 provides a summary of the specific detectivity ( D n *) of NIR-OPDs at similar wavelengths. Notably, our OPDs fabricated from ZnO:PDINO hybrid ETL exhibit the highest D n * under the same operating conditions in the PTB7-COTIC-4F system.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Our overall performance analyses of OPD with PDINO as a hybrid blend in ETL indicate that PDINO significantly contributes as a cathode interlayer. For comparison of our results, Table provides a list of the recent state-of-the-art reports on high-performance NIR-OPD while Figure S11 provides a summary of the specific detectivity ( D n *) of NIR-OPDs at similar wavelengths. Notably, our OPDs fabricated from ZnO:PDINO hybrid ETL exhibit the highest D n * under the same operating conditions in the PTB7-COTIC-4F system.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For instance, Yoo et al reported a CPDT-based p-type CP that displayed NIR absorption from 700 nm to 1000 nm and ambipolar charge transport with high hole mobility of 1.50 cm 2 V -1 s -1 [17] . Similarly, Bhat et al developed an NIR organic photodiode (OPD) using a CPDT-based p-type CP, which exhibited broad absorption around 1200 nm and an NIR photocurrent responsivity of 0.4 mA W -1 at -2 V under 1050 nm illumination [18] .…”
Section: Introductionmentioning
confidence: 99%